Microbial biopesticides and pest management - Parmar G.M.; Jadav N.B. (New Delhi Kalyani, 2011)
the aim of book is to have greater farmer acceptance of microbial biopesticides
microbial control biopesticides global demand trichoplusia ni bioefficacy nomuraea
Keywords: microbial control, biopesticides global demand